Correlation Of Patients' Knowledge Regarding Diabetes with Their Glycaemic Control: A Cross-Sectional Study from An Urban Area - Chidanand D Awalekar; Vivek B Waghachavare; Jayshree C Awalekar; Manohar Chavan; Vishwajeet M Chavan; Madhavi Patwardhan (Medsci Publications, 2016)
Introduction: Diabetes is a chronic condition requiring lifelong management, associated with increased mortality and morbidity. It is important for diabetic patients to have knowledge regarding the disease and self-care. The objective of current study was studying correlation of patients' knowledge regarding diabetes with their glycaemic control. Methods: It is a cross-sectional study conducted among the patients attending a diabetic clinic in a tertiary care hospital, from Sangli City (Maharashtra).The study tool was pretested and self- administered questionnaire. Analysis was done using Microsoft Excel and SPSS- 22. Results: Of the 573study participants, only 114 (19.9%) had fasting plasma glucose level ≤ 130 mg/dl. Considering the knowledge regarding diabetes; 46.4% participants had scored less than 50%, while only 12.9% participants had scored >75%. The participants with fasting plasma glucose level at ≤130 mg/dl had highest mean knowledge score. On examining with Pearson correlation; the knowledge regarding diabetes had a positive correlation with the period of diabetes morbidity and a negative correlation with fasting plasma glucose. Conclusion: The knowledge regarding diabetes was helpful in achieving better glycaemic control. Hence efforts should be made to increase the diabetes related literacy among the patients.